JALUR DISTRIBUSI KAYU MAHONI SEBAGAI BAHAN BAKU KERAJINAN DARI SAWMILL SAMPAI KE PENGRAJIN DI KECAMATAN TAMPAKSIRING - Surya Wirawan, I Kadek; Wrasiati, Luh Putu; Sadyasmara, Cokorda Anom Bayu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2019)
This study aimed to know the path of wood distribution produced from Sawmill, Tampaksiring District to the craftsman. This study also aimed to know the handling of wood in every distribution path that was being passed, to know the marketing margin and profit of each tracks from Sawmill to the craftsman. In this research used the survey method by using questionnaires distributed to Sawmill, traders 1, traders 2, retailers, craftsmen. The result of this study found that there was 4 path of wood distributions from Sawmill, Tampaksiring District to the craftsman, there were: I) Farmers – Traders –Consumers, II) Farmers – Traders1 – Traders – Consumers, III) Farmers – Collectors – Traders – Retailers – Consumers, IV) Farmers – Traders – Retailers – Consumers. There was not tracks of wood distribution consisted of sorting and grading on collectors and traders, lowest margin and profit margin of all path on line I are: Rp.850.340 / m 3 and Rp.380.000 / m 3 . While the margin and profit margin of all paths on line IV are: Rp.1.950.630 / m 3 and Rp.900.000 / m 3 . Key words : distribution path, wood mahoni, craftsman, Sawmill .